👤

Salut tout le monde !Supprime les parenthèses puis réduis les expressions suivantes:
A=5+(2n+3)
B=5n-(3-4n)
C=(n-4)-6
D=(4n+2)+(-6n-2)
E=-(-3n-1)+(n-3)
F=8n-(5n+2)+(3-4n)

Merci d'avance


Répondre :

Bonjour,

Supprime les parenthèses puis réduis les expressions suivantes :

A=5+(2n+3)
A = 5 + 2n + 3
A = 2n + 8

B=5n-(3-4n) 
B = 5n - 3 + 4n
B = 9n - 3

C=(n-4)-6 
C = n - 4 - 6
C = n - 10

D=(4n+2)+(-6n-2) 
D = 4n + 2 - 6n - 2
D = - 2n 

E=-(-3n-1)+(n-3) 
E = 3n + 1 + n - 3
E = 4n - 2

F=8n-(5n+2)+(3-4n)
F = 8n - 5n - 2 + 3 - 4n
F = - n + 1
A=5+2n+3
A=2n+5+3
A=2n+8
B=5n-3+4n
B=5n+4n-3
B=9n-3
C=n-4-6
C=n-10
D=4n+2-6n-2
D=4n-6n+2-2
D=-2n
E=3n+1+n-3
E=4n-2
F=8n-5n-2+3-4n
F=8n-5n-4n-2+3
F=-n+1